Error and the academic self : the scholarly imagination, medieval to modern - Lerer, Seth, 1955- (New York : Columbia University Press, 2002)
-- ACLA, 3/11/05.
Introduction : the pursuit of error : philology, rhetoric, and the history of scholarship -- Errata : mistakes and masters in the early modern book -- Sublime philology : an elegy for Anglo-Saxon studies -- My Casaubon : the novel of scholarship and Victorian philology -- Ardent etymologies : American rhetorical philology, from Adams to de Man -- Making mimesis : exile, errancy, and Erich Auerbach -- Epilogue : Forbidden Planet and the terrors of philology.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: English philology -- History; Great Britain -- Intellectual life; Scholarly publishing -- Great Britain; Errors and blunders, Literary -- History; English literature -- History and criticism -- Theory, etc; American literature -- History and criticism -- Theory, etc; Error -- History; Philologie anglaise -- Histoire; Grande-Bretagne -- Vie intellectuelle; Édition savante -- Grande-Bretagne.; Erreurs et bévues littéraires -- Histoire; Littérature américaine -- Histoire et critique -- Théorie, etc; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; LITERARY CRITICISM -- European -- General; English literature -- Theory, etc; English philology; Error; Errors and blunders, Literary; Intellectual life; Scholarly publishing; Great Britain; Criticism, interpretation, etc; History